2016
DOI: 10.3892/or.2016.4869
|View full text |Cite
|
Sign up to set email alerts
|

COL11A1 is overexpressed in recurrent non-small cell lung cancer and promotes cell proliferation, migration, invasion and drug resistance

Abstract: Abstract. Collagen type XI α1 (COL11A1), a minor fibrillar collagen, has been demonstrated to be involved in cell proliferation, migration and the tumorigenesis of many human malignancies. Previous studies have shown that COL11A1 may be a valuable diagnostic marker for non-small cell lung carcinoma (NSCLC). However, its biological function in NSCLC progression remains largely unclear. In the present study, we investigated the expression levels of COL11A1 in different human NSCLC samples, and found that COL11A1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
68
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 36 publications
0
68
0
Order By: Relevance
“…Thus, it is highly likely that a B-Myb-CCNA1 regulatory loop also exists and plays an important role in NSCLC cells. COL11A1 , COL6A1 , MMP2 , NID1 , and FLT4 have been shown to have a positive role in regulating motility and invasion of various cancer cells [26,27,28,29,30,31]. Moreover, we also found that the deregulated genes affected by B-Myb overexpression could be enriched in ERK and Akt signaling pathways.…”
Section: Discussionmentioning
confidence: 55%
“…Thus, it is highly likely that a B-Myb-CCNA1 regulatory loop also exists and plays an important role in NSCLC cells. COL11A1 , COL6A1 , MMP2 , NID1 , and FLT4 have been shown to have a positive role in regulating motility and invasion of various cancer cells [26,27,28,29,30,31]. Moreover, we also found that the deregulated genes affected by B-Myb overexpression could be enriched in ERK and Akt signaling pathways.…”
Section: Discussionmentioning
confidence: 55%
“…In lung cancer, it has a positive correlation with pathology stage, poor prognosis, and lymph node metastasis (Chong et al, ), it promotes ovarian cancer progression and chemoresistance to cisplatin and paclitaxel via activating NF‐KB , and it promotes the expression of TWIST1 , MCL1( Wu, Huang, Chang, & Chou, ). It has also been reported that COL11A1 was upregulated in gastric cancer and non‐small cell lung cancer which could boost the malignant behavior in vitro (Li, Li, Lin, Zhuo, & Si, ; Shen et al, ). COL11A1 could be utilized as a promising biomarker in predicting malignant relapse of breast intraductal papilloma (Freire et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…Here, the significant mutations of SMARCA4 were also related with the poor survival rate of one LUAD subtype (Figure 4), and the mutations may lead to decreased expressions of SMARCA4 (see Additional file 1). Similarly, KEAP1 [40], TP53 [41] and COL11A1 [33] have all been reported to play roles in LUAD. Co-occurrence of these SMGs in the poor survival subtype implies that the differential prognosis between the two subtypes is not simply the result of one specific gene but a collection of meaningful genes.…”
Section: Discussionmentioning
confidence: 91%